2010
DOI: 10.1007/s10344-010-0474-x
|View full text |Cite
|
Sign up to set email alerts
|

Diet quality and immunocompetence influence parasite load of roe deer in a fragmented landscape

Abstract: International audienceThe influence of landscape structure and host diet on parasite load of wildlife is still largely unknown. We studied a roe deer () population in a fragmented agricultural landscape in southern France to explore the relationship of gastrointestinal nematode load with spleen mass (to index immunocompetence), faecal nitrogen (to index diet quality), landscape structure and age of 33 hunt-harvested roe deer. Gastrointestinal worm counts were negatively related to faecal nitrogen and spleen ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 39 publications
(46 reference statements)
1
12
1
Order By: Relevance
“…The rate of encounters can vary with the level of host foraging activities [ 23 , 24 ], the characteristics of the host habitat [ 25 27 ], the spatial and temporal co-distributions of hosts and vectors [ 28 31 ]. Similarly, the rate of parasite success in the host can depend on the individual level of immunity [ 32 34 ] or physiological status [ 35 38 ].…”
Section: Resultsmentioning
confidence: 99%
“…The rate of encounters can vary with the level of host foraging activities [ 23 , 24 ], the characteristics of the host habitat [ 25 27 ], the spatial and temporal co-distributions of hosts and vectors [ 28 31 ]. Similarly, the rate of parasite success in the host can depend on the individual level of immunity [ 32 34 ] or physiological status [ 35 38 ].…”
Section: Resultsmentioning
confidence: 99%
“…For deer inhabiting predominantly agricultural habitats, this could lead to a reduction in metabolic costs associated with digestion, and consequently a reduction in daily energy expenditure allocated for rumination. The better body condition (Hewison et al 2009) and immunocompetence (Navarro-Gonzalez et al 2011) of roe deer living in the more open landscapes of our study area could therefore be partly explained by this energetic advantage. Whether the landscape-related differences in digestive tissue mass observed in this study could suffice to result in significant metabolic savings needs to be explored in future studies by measuring and modeling energy expenditure and intake.…”
Section: Discussionmentioning
confidence: 95%
“…This was explained as an investment in the production and stockage of lymphocytes in the spleen in order to counteract potential infections (Møller et al, 1998). However, other studies have suggested that spleen mass reflects the host condition and therefore should be negatively related to parasite infection (Corbin et al, 2008;Lutermann and Bennett, 2008;Navarro-Gonzalez et al, 2011). However, these hypotheses are not mutually exclusive.…”
Section: Impacts Of Parasites and Parasite Risk On Spleen Size And Inmentioning
confidence: 99%